Dual‐output dc–dc buck converters with bidirectional and unidirectional characteristics. Issue 5 (1st May 2013) - dos Santos, Euzeli Cipriano
Abstract : This study presents single‐input double‐output unidirectional and bidirectional dc–dc buck converters, for applications that demand two dc‐controlled output voltages. The proposed converters present a component count reduction and it is considered as a monolithic device with two output voltages generated by the same power converter. The main advantages of the proposed converters are reduction of costs and better power losses distribution among the semiconductor devices. Besides the proposal of suitable power converters, this study presents their models, control strategies, modulation approaches and design specification. The selected simulated and experimental results are presented as well.